The relationship between corruption, ease of doing business and FDI inflows in SADC countries - Matete, Desmond (Graduate School of Business (GSB), 2022)
Globalisation and trade integration have positioned Foreign Direct Investment (FDI) as a development imperative for many developing countries, including Southern African Development Community (SADC) economies. Despite concerted efforts both at individual country level and at regional level, FDI flows to the SADC region have declined compared to other regions in the world. The main reasons posited for SADC's inability to attract and retain FDI include negative risk perceptions; a weak ease of doing business environment, and endemic corruption. Hence, the study seeks to investigate the relationship between FDI inflows and corruption and ease of doing business in SADC. The research applies Generalised Method of Moments (GMM) analysis to all 16 SADC countries over a period of 2010 to 2019. The results show that although both corruption and ease of doing business are significantly and positively relate to FDI inflows in SADC, ease of doing business affects FDI to a greater extent compared to corruption. In addition, the inclusion of the interaction between corruption and ease of doing business shows that FDI inflows are more closely attracted by ease of doing business than by corruption.